2018
DOI: 10.1186/s12876-018-0786-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic and apoptotic activity in colorectal neoplasia

Abstract: BackgroundColorectal cancer (CRC) is third most commonly diagnosed cancer worldwide. The aim of the prospective study was to evaluate mitosis and apoptosis of epithelial cells at each stage of colorectal neoplasia.MethodsA total of 61 persons were enrolled into the study: 18 patients with non-advanced colorectal adenoma (non-a-A), 13 patients with advanced colorectal adenoma (a-A), 13 patients with CRC and 17 controls: individuals with normal findings on colonoscopy. Biopsy samples were taken from pathology (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Mitotic dysregulation and the cell cycle play an essential role in cancer progression. Kohoutova et al also demonstrated that apoptosis, cell cycle, and mitosis were significantly dysregulated during CRC tumor progression, [ 19 ] which is also in line with the findings of this study.…”
Section: Discussionsupporting
confidence: 92%
“…Mitotic dysregulation and the cell cycle play an essential role in cancer progression. Kohoutova et al also demonstrated that apoptosis, cell cycle, and mitosis were significantly dysregulated during CRC tumor progression, [ 19 ] which is also in line with the findings of this study.…”
Section: Discussionsupporting
confidence: 92%
“…E. coli from patients with non-advanced adenoma differed from E. coli of healthy controls and patients with advanced adenoma/carcinoma in several tested determinants, including virulence factors and E. coli phylogroups ( Supplementary Table 3 ). As we showed in previous study, non-advanced adenomas were histologically different from both the healthy tissue and advanced adenomas ( Kohoutová et al, 2018 ). Moreover, differences in intestinal microbiota in the early stages of neoplasia were shown by Nakatsu et al (2015) .…”
Section: Discussionsupporting
confidence: 56%
“…Dysregulation of epithelial proliferation and apoptosis is typical for a neoplastic process. Kohoutova et al demonstrated that mitosis and apoptosis are dysregulated in intestinal adenomas, and that this dysregulation is triggered by genetic alterations [ 56 ]. Among the top 30 results of KEGG pathway enrichment analysis, the pathways in cancer, lipid and atherosclerosis, PI3K-Akt signaling pathway, and MAPK signaling pathway are the most relevant to CRA.…”
Section: Discussionmentioning
confidence: 99%